Employability Skill dan Grit Terhadap Kesiapan Kerja yang Dimoderasi Informasi Dunia Kerja - Puteri, Deshea Vernanda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The objective of this research is to explain the effects of employability skill and grit on the occupational readiness of the final-year students of Faculty of Administration Science of Universitas Brawijaya with information about working world as the moderator. Using probability sampling method and proportionate stratified random sampling, 96 people were selected as the respondents of this explanatory research. The data was harvested via Likert-scaled questionnaires and the analysis was performed in SPSS version 25. This study finds that (1) employability skill and grit simultaneously have significant impacts on the occupational readiness of the final-year students, (2) that employability skill positively and significantly affects the occupational readiness of the final-year students, (3) that grit has no significant influence on the occupational readiness of the final-year students, (4) that information about working world moderates (weakens) the relationship between employability skill and the occupational readiness of the final-year students, and that (5) information about working world does not moderate the impact of grit on the occupational readiness of the final-year students. Furthermore, this study also reveals that the coefficient of determination for the occupational readiness of the final-year students of Faculty of Administration Science of Universitas Brawijaya is 73.4%. Abstrak Penelitian ini bertujuan untuk menjelaskan pengaruh employability skill dan grit terhadp kesiapan kerja mahasiswa akhir Fakultas Ilmu Administrasi Universitas Brawijaya dengan informasi dunia kerja sebagai pemoderasi. Penelitian ini merupakan penelitian explanato-ry research. Teknik pengumpulan data menggunakan kuesioner, Teknik sampling yang digunakan adalah probability sampling dengan metode proportionate stratified random sampling. Sampel yang digunakan dalam penelitian ini berjumlah 96 orang dan dianalisis menggunakan software SPSS versi 25. Skala yang digunakan dalam penelitian ini adalah skala likert. Hasil penelitian ini menunjukkan bahwa: (1) Employability skill dan Grit secara simultan berpengaruh positif dan signifikan terhadap kesiapan kerja mahasiswa tingkat akhir, (2) Employability skill memiliki pengaruh positif dan signifikan terhadap kesiapan kerja mahasiswa tingkat akhir, (3) Grit tidak berpengaruh signifikan terhadap kesiapan kerja mahasiswa tingkat akhir, (4) Informasi Dunia Kerja mampu memoderasi (melemahkan) hubungan antara employability skill dengan kesiapan kerja mahasiswa tingkat akhir, (5) Informasi Dunia kerja tidak mampu memoderasi pengaruh grit terhadap kesiapan kerja mahasiswa tingkat akhir.Penelitian ini mengungkapkan hasil koefisien de-terminasi sebesar 73,4% terhadap kesiapan kerja mahasiswa tingkat akhir Fakultas Ilmu Administrasi Universitas Brawijaya.